2019
DOI: 10.1186/s13063-019-3307-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Feasibility of Pain management and Patient Education for Physical Activity in Intermittent claudication (PrEPAID): protocol for a randomised controlled trial

Abstract: Background Physical activity (PA) improves functional capacity and quality of life and provides secondary prevention benefits in individuals with peripheral arterial disease (PAD) and intermittent claudication (IC). However, pain and patient lack of knowledge are key barriers to the uptake of, and adherence to, PA recommendations. This trial will test the efficacy and feasibility of a non-invasive pain management intervention with and without patient education to improve PA in individuals with PAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Although other studies found no differences, this fact may be due to a lack of adherence to lipid-lowering drug treatments, as well as to the prescribed drug plan [ 58 , 59 ]. This is one of the main barriers that health professionals face, together with a lack of knowledge or a lack of a personalised follow-up [ 60 , 61 ]. Focusing efforts at the individual level improves adherence and therapeutic management.…”
Section: Discussionmentioning
confidence: 99%
“…Although other studies found no differences, this fact may be due to a lack of adherence to lipid-lowering drug treatments, as well as to the prescribed drug plan [ 58 , 59 ]. This is one of the main barriers that health professionals face, together with a lack of knowledge or a lack of a personalised follow-up [ 60 , 61 ]. Focusing efforts at the individual level improves adherence and therapeutic management.…”
Section: Discussionmentioning
confidence: 99%
“…A t-test power analysis determined that at least 36 subjects were required to obtain a power of 0.8 at a two-sided level of 0.05 with effect size d = 0.8 [19]. This analysis was based on data derived from previous literature [20]. The Shapiro-Wilk test was used to check distribution of the analysed variables; differences between variables with normal distribution were assessed via the Student's t-test; the non-parametric Mann-Whitney U test or the Wilcoxon signed-rank test were employed in the case of variables…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the recruitment rate, the study screening log will record the reasons for unquali ed and non-recruitment patients. Retention and reasons for the withdrawal of participants throughout the trial will be documented [34]. The outcome measures will be described according to Fig.…”
Section: Data Collection and Managementmentioning
confidence: 99%
“…Figure 1 Retention and reasons for the withdrawal of participants throughout the trial will be documented [34]. The outcome measures will be described according to Figure1.…”
Section: Declarations Trial Statusmentioning
confidence: 99%